PYRUVATE OXIDATION BY PASTEURELLA TULARENSIS STRAINS OF GRADED VIRULENCE - Weinstein, I. (1962)
Weinstein, I. (U.S. Army Chemical Corps, Fort Detrick, Frederick, Md.), M. L. Guss, and R. A. Altenbern. Pyruvate oxidation by Pasteurella tularensis strains of graded virulence. J. Bacteriol. 83:1010–1016. 1962.—The rate of oxidation of sodium pyruvate by Pasteurella tularensis was shown to be correlated with the virulence of the strain studied. No qualitative differences in cofactor requirements for or products of pyruvate oxidation were found among strains of graded virulence. The rate of pyruvate oxidation was directly related to strain virulence, whereas the endogenous respiration rate was inversely correlated with virulence. For all tested strains possessing some degree of virulence, maximal rates of pyruvate oxidation were obtained with small concentrations of pyruvate (10 to 20 μmoles), above which the oxidation rate was depressed. Small concentrations of glutamate or other dicarboxylic acids effected nonadditive stimulation (sparking) of the pyruvate oxidation rate only at pyruvate concentrations above optimal (greater than 20 μmoles). The avirulent strain 38A was unique, being characterized by a low endogenous respiration rate, a maximal rate of pyruvate oxidation at all concentrations above 20 μmoles, and the absence of glutamate sparking. Studies of cell-free extracts indicated that the differences in pyruvate oxidation among the strains may be attributed in part to variation in the properties of enzymes of the tricarboxylic acid cycle.